Portuguese military procurement during the colonial war: (1961-1974) - Timóteo, João Pedro Gomes (2020)
Portugal’s colonial war was a low-intensity, long-lasting conflict fought in three separate, noncontiguous theaters of operation. This led Portugal during the Colonial War to mobilize the largest number of men per capita of any western country, except for Israel. They rotated over 820,000 men through combat deployments in the colonies, having had over 120,000 troops deployed concurrently. For that, they required a large number of arms and equipment to carry on the fight, which lasted throughout the 1960s and only came to an end after a coup d’état deposed the Portuguese regime in 1974. The acquisition of these weapons, however, was complicated by the diplomatic siege that had been erected against Portugal. The Portuguese actions in the colonies were cause for much outrage, leading to open condemnation and, more importantly, as this dissertation is concerned, to a significant arms embargo, which was adhered to by many of Portugal’s own allies, such as the United States. This study seeks to investigate some of the sources Portugal used to supply its military, paying special attention to the pivotal role played by the FRG.